Improving food composition data by standardizing calculation methods - Öhrvik, Veronica (TemaNord, 2015)
Food composition data is important in nutritional policy making. However, food analyses are expensive and to use analysed values only is not economically justifiable; hence recipe calculations are important for the quality of food composition databases. The aim with this project, financed by the Nordic Council of Ministers, was to improve and standardize the recipe calculation method. A general recipe calculation method was developed, implemented and validated by comparing analysed and calculated content. The method and the foods recalculated within the project will be used in national dietary surveys and are available to the public through the national food composition databases. This report may be used as a guide through recipe calculations. Furthermore, the importance of well-structured methods for recipe calculations and possible consequences otherwise are highlighted.